Character Building In Cultural Perspective and Implementation - Suheri Sahputra Rangkuti; Zulhimma Zulhimma; Zulhammi Zulhammi (STAI Hubbulwathan Duri, 2022)
This article contains the discourse on character building from a cultural perspective. Character building, which is generally only done through classroom education, is considered insufficient to instill awareness and moral action of students. Meanwhile, culture with all its value content, in theory, is more easily absorbed in everyday experience because culture is part of the experience itself. This article was written in order to offer a new perspective that is effective in instilling cultural values. Because so far the formation of cultural character only stops in the classroom. The research method used in this article is library research with a philosophical analysis approach. In this case, the education of cultural values is seen in the dynamics of character decline and the decline of culture after that dialogue between character values, society and cultural morals in order to find effective ways to implement character building. The results of this study confirm that the formation of character in a cultural perspective tends to make it easier for generations in a culture to read values and make it a continuous moral action because the formation offered by culture is not only in the realm of imagination and cognitive, even participation and cultural guidance present morals. in the experience of the individual in each generation of community groups.